Menanamkan Nilai-Nilai Pendidikan Patriotisme pada Mahasiswa - Toni Toni; Panggih Nur Adi; Ilham Hakiki Harahap (JURNAL PEMBELAJARAN DAN MATEMATIKA SIGMA (JPMS), 2022)
The purpose of this study was to determine the educational values of patriotism in students of the PPKn Study Program at Labuhanbatu University. The approach used in this research is a qualitative research type, with a descriptive approach because this research is to describe and explain about the education of patriotism character values that are obtained directly and in real terms through interviews. structured towards students of the 1st (one) semester PPKn Study Program which is carried out for one month. Data collection methods used in the research included observation, interviews and documentation. The results of the study concluded regarding the process of instilling patriotism educational values obtained during structured interviews with material that had been prepared beforehand, many students did not understand the material. Such as material about (1) Willing to sacrifice which is interpreted as a form of fighting spirit to defend the country from enemy threats, (2) Defending the country such as national defense reserves or conscription for every citizen if needed for the integrity of the Indonesian nation, (3) love of the motherland such as commemorating the independence day of the Indonesian nation, maintaining the unity of the Indonesian republic and not being divided, and (4) Pancasila as the state ideology in which there are five precepts that must be carried out in every joint of the country. Pancasila as a unifying nation and the foundation of a country to maintain the integrity of a nation and instill nationalism and patriotism of the nation.